2020
DOI: 10.1038/s41598-020-72634-y
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the flux of reactive species: a case study on thin film deposition in an aniline/argon plasma

Abstract: The plasma based synthesis of thin films is frequently used to deposit ultra-thin and pinhole-free films on a wide class of different substrates. However, the synthesis of thin films by means of low temperature plasmas is rather complex due to the great number of different species (neutrals, radicals, ions) that are potentially involved in the deposition process. This contribution deals with polymerization processes in a capacitively coupled discharge operated in a mixture of argon and aniline where the latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…On the practical side, applications range from the synthesis of polymers [6], nanostructures [7], and functionalized nanoparticles [8] to contamination control in photolithography [9,10] and plasma diagnostics [11].…”
Section: Introductionmentioning
confidence: 99%
“…On the practical side, applications range from the synthesis of polymers [6], nanostructures [7], and functionalized nanoparticles [8] to contamination control in photolithography [9,10] and plasma diagnostics [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was moreover demonstrated that argon/aniline plasmas contain negative ions, which are formed through complex surface reactions with the electrodes, requiring a wall conditioning for a stable deposition process. [64,65] It can be expected that many parameters (pressure, power, gas flow, pumping speed, pulse frequency, and duty cycle) as well as reactor engineering aspects (dimensions, materials, or electrodes geometry) will impact the discharge properties and thus the thin-film deposition. However, one of the most important parameters (for a given power) is the gas mixing ratio, i.e.…”
Section: Introductionmentioning
confidence: 99%